2014
DOI: 10.1212/wnl.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Untreated brain arteriovenous malformation

Abstract: Objective: To identify risk factors for intracranial hemorrhage in the natural history course of brain arteriovenous malformations (AVMs) using individual patient data meta-analysis of 4 existing cohorts.Methods: We harmonized data from Kaiser Permanente of Northern California (n 5 856), University of California San Francisco (n 5 787), Columbia University (n 5 672), and the Scottish Intracranial Vascular Malformation Study (n 5 210). We censored patients at first treatment, death, last visit, or 10-year follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
191
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(217 citation statements)
references
References 23 publications
5
191
2
4
Order By: Relevance
“…Patients with <12 months follow-up who developed complications were also included. To select patients for the ARUBA-eligible cohort, the following exclusion criteria were applied 1 : Previous AVM hemorrhage, 2 any previous AVM intervention including embolization or microsurgery 3 age <18 years, 4 life expectancy <10 years (age >66 years for men or >71 years for women), 5 and Spetzler-Martin grade V AVMs. 12 …”
Section: Methods Patient Selection For the Aruba-eligible Cohortmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with <12 months follow-up who developed complications were also included. To select patients for the ARUBA-eligible cohort, the following exclusion criteria were applied 1 : Previous AVM hemorrhage, 2 any previous AVM intervention including embolization or microsurgery 3 age <18 years, 4 life expectancy <10 years (age >66 years for men or >71 years for women), 5 and Spetzler-Martin grade V AVMs. 12 …”
Section: Methods Patient Selection For the Aruba-eligible Cohortmentioning
confidence: 99%
“…The annual hemorrhage risk of the conservatively managed patients in ARUBA was 2.2%, which is consistent with previous natural history studies but higher than the 0.9% annual hemorrhage rate observed during the latency period of our cohort. 2,18,19 Because 30% of the patients with in this study were determined to have an unfavorable outcome (incomplete AVM obliteration, hemorrhage during the latency period, or permanent treatment-related complication), we estimate that patients who undergo radiosurgery would have superior outcomes to observation after 17 years of follow-up. This estimate does not account for other neurological sequelae originating from a patent AVM, such as seizures and focal deficits secondary to chronic vascular steal.…”
Section: February 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] A recent angiographic study revealed that the angioarchitectural features of BAVM, some of which confer a higher risk for future hemorrhage in adults, differ between children and adults. 7 However, only a few studies have specifically been conducted to assess the risk of pediatric BAVM hemorrhage and provide a prognosis before treatment (On-line Table 3).…”
Section: Bavm Hemorrhage Risk Predictors In Pediatric Patientsmentioning
confidence: 99%
“…[8][9][10] Meta-analyses of natural history studies and large-scale cohort studies failed to reach a consensus regarding the role of other factors such as nidus size, exclusive deep venous drainage, associated arterial aneurysm, and deep location. [11][12][13] A periventricular location has also been found to correlate positively with the risk of hemorrhage before the treatment of BAVMs. 14,15 However, this feature, although amenable to analysis with imaging, has not been studied carefully in the risk assessment of interventional-versus-observational treatment.…”
mentioning
confidence: 98%